2021
DOI: 10.3390/molecules27010230
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Bioactive Flavonoid Hybrids Linked by 1,2,3-Triazole Ring Obtained by Click Chemistry

Abstract: As a result of the biological activities of natural flavonoids, several synthetic strategies aiming to obtain analogues with improved potency and/or pharmacokinetic profile have been developed. Since the triazole ring has been associated with several biological activities and metabolic stability, hybridization with a 1,2,3-triazole ring has been increasingly reported over the last years. The feasible synthesis through copper (I) catalyzed azide-alkyne cycloaddition (CuAAC) has allowed the accomplishment of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 127 publications
0
21
0
Order By: Relevance
“…17,[19][20][21][22][23] In this sense, triazoles compounds, as chemical intermediates, are broadly utilized in numerous industrial formulations including biological and pharmaceutical ones. 24,25 Towards this end, various approaches have been utilized to synthesize 1,2,3triazole moieties. [26][27][28] Moreover, the catalytic Huisgen 1,3dipolar cycloaddition of epoxides, thiiranes and aziridines with NaN 3 and terminal alkynes generated the corresponding 1,2,3triazoles, considered as one of the most relevant methods.…”
Section: Introductionmentioning
confidence: 99%
“…17,[19][20][21][22][23] In this sense, triazoles compounds, as chemical intermediates, are broadly utilized in numerous industrial formulations including biological and pharmaceutical ones. 24,25 Towards this end, various approaches have been utilized to synthesize 1,2,3triazole moieties. [26][27][28] Moreover, the catalytic Huisgen 1,3dipolar cycloaddition of epoxides, thiiranes and aziridines with NaN 3 and terminal alkynes generated the corresponding 1,2,3triazoles, considered as one of the most relevant methods.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are well-known to possess a variety of biological activities with therapeutic interests such as antioxidant [ 5 ], antimalarial [ 6 ], anti-inflammatory [ 7 , 8 ], antiviral [ 9 , 10 ], antibacterial [ 11 ], antidiabetic [ 8 ], antifungal [ 12 ], and anticancer [ 1 , 13 , 14 , 15 , 16 ] potential. It is also reported that they protect the cardiovascular system from oxidative stress as a consequence of their ROS scavenger ability [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavones containing a 2-phenylchromen-4-one ( 1 ) backbone, and 1,2,3-triazole derivatives keep attracting much research interest, and many 1,2,3-triazole-containing hybrids are known as effective anticancer agents [ 12 , 13 , 14 , 15 ]. During the last decade, numerous biologically active flavone—1,2,3-triazole hybrids have been synthesized [ 16 , 17 , 18 ], for example, 5 apigenin-7-methyl ether derivative, which showed promising activity against ovarian cancer ( IC 50 = 10, 15 and 20 µM for SKOV3, OVCAR-3 and Caov-3 cancer cell lines) ( Figure 1 ) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%